The Pastoral Role in Developing Youth Participation in the GMIH Eben Haezer Tuguis Congregation, South Loloda Region - Silvia Shorea Mauwilik; Daniel Susanto; Steve Gaspersz (Program Pascasarjana UKIM, 2025)
This thesis aims to determine the factors causing the low participation of young men and women in church services at the GMIH Eben-Haezer Tuguis Congregation. This research uses a qualitative approach with a case study method. Data were collected through interviews, observations, and document studies. The results of the study indicate that low participation is caused by two factors: internal factors and external factors. Both fear, anxiety, and shame that arise from oneself due to ignorance, ministry trauma, bullying , minimal pastoral care from the church, and family also contribute to the impact. The church has a significant role in seeing the lives of the congregation, especially through three dimensions of its service: koinonia (fellowship), marturia (witness), and diakonia (service). In this context, youth are also an integral part of the Body of Christ and are called to take an active part in church life, as the future generation of the church. Many factors influence and become causes, which encourage every church leader to look at this. Therefore, This study suggests an empowerment-based pastoral approach so that youth can experience healing, growth, and active involvement.